Teachers` Self-Efficacy and Classroom Management in Community Learning Centre (CLC) Sarawak - Ciptro Handrianto; Shahid Rasool; M Arinal Rahman; Musta`in Musta`in; Aldeva Ilhami (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Community Learning Centre (CLC) is the Indonesian government's primary education to the children of Indonesian migrant workers in palm oil plantations in Sarawak, Malaysia. Teachers` self-efficacy and classroom management are important issues in education, including for Indonesian children overseas. Self-efficacy means that the belief of teachers to perform good quality and competency in teaching-learning practices. The teachers who have high self-efficacy may be able to solve problems faced by students. They have the confidence to find out the solutions effectively. Meanwhile, classroom management is a teacher's efforts to supervise classroom activities such as training, group interaction, and learner performance. The successful study is determined how far the teacher can manage their classes. A good class is not a silent class, but making more participating in the teaching-learning process. In CLC Sarawak's context, teachers` self-efficacy and classroom control are the key concepts to enhance Indonesian students' learning. There are some beneficial impacts for the students if their teachers have self-efficacy highly and promising approach in classroom management, namely: (1) Students meet a figure who can be trusted and help to solve their problems; (2) Students enjoy in the teaching-learning process because the teachers bring them the simplicity from complex materials and concept; (3) Students are more confident and actively to participate in their classroom; (4) Students will have critical thinking and can quickly answer the questions; (5) Students have high motivation and try their best in the study for their success in the future.